Production and preservation of resins – past and present. (4th May 2018) - Seyfullah, Leyla J.; Beimforde, Christina; Dal Corso, Jacopo; Perrichot, Vincent; Rikkinen, Jouko; Schmidt, Alexander R.
ABSTRACT: Amber is fossilised plant resin. It can be used to provide insights into the terrestrial conditions at the time the original resin was exuded. Amber research thus can inform many aspects of palaeontology, from the recovery and description of enclosed fossil organisms (biological inclusions) to attempts at reconstruction of past climates and environments. Here we focus on the resin itself, the conditions under which it may have been exuded, and its potential path to fossilisation, rather than on enclosed fossils. It is noteworthy that not all plants produce resin, and that not all resins can (nor do) become amber. Given the recent upsurge in the number of amber deposits described, it is time to re‐examine ambers from a botanical perspective. Here we summarise the state of knowledge about resin production in modern ecosystems, and review the biological and ecological aspects of resin production in plants. We also present new observations on conifer‐derived resin exudation, with a particular focus on araucarian conifer trees. We suggest that besides disease, insect attacks and traumatic wounding from fires and storms, other factors such as tree architecture and local soil conditions are significant in creating and preserving resin outpourings. We also examine the transformation of resin into amber (maturation), focusing on geological aspects of amber deposit formation and preservation. We present new evidence that expands previous understanding of amber deposit formation. Specific geological conditions such as anoxic burial are essential in the creation of amber from resin deposits. We show that in the past, the production of large amounts of resin could have been linked to global climate changes and environmental disruption. We then highlight where the gaps in our knowledge still remain and potential future research directions.